Immediate effect of non-invasive auricular acupoint stimulation on the performance and meridian activities of archery athletes: A protocol for randomized controlled trial. Issue 8 (26th February 2021) - Tsai, Yi-Hsun; Wu, Szu-Ying; Hu, Wen-Long; Lai, Yun-Ru; Tsao, Yu; Yen, Ke-Tien; Lin, Cheng-Hsien; Kuo, Chun-En Aurea
Abstract: Background: Archery has existed in human history for millenniums. Being a unique exercise and precision sport, the keys to performance are emotional control, attention, and concentration rather than explosive force, muscle power, and endurance. During the execution of archery, attention is the key to performance in elite players, especially in the initial period while drawing the bow. Auricular acupoint stimulation is one of the therapeutic methods of traditional Chinese medicine and has been reported for its use in amplifying the anesthesia effect, weight reduction, cessation of substance abuse, and autonomic nervous modulation. Methods: The study will recruit archery players in school teams among junior and senior high schools and colleges. The subjects will be randomly assigned to the ear and sham acupressure groups. This is a randomized controlled trial with crossover design. The outcome measures will be obtained, including the meridian activities and balance index with Ryodoraku device, the movement stability with WIMU tracking system, the continuous heart rate record, and the scores of the 2 sections as the performance. The subjects will rate their attention and fatigue levels through self-reported questionnaires. Objectives: This study aims to investigate the immediate effect of non-invasive auricular acupoint stimulation on the performance and meridian activities of archery athletes. Trial registration: ClinicalTrials.gov Identifier: NCT04637607.